Waste to energy - Syngellakis, S. (WIT Press, 2015)
Waste to Energy" deals with the very topical subject of converting the calorific content of waste material into useful forms of energy. It complements and, to a certain degree, overlaps with its companion volume, "Biomass to Biofuels", since a significant proportion of biomass converted to energy nowadays originates from various types of waste. The material in the first, more substantial part of the volume has been arranged according to the type of process for energy conversion. Biochemical processes are described in six articles. These relate to the production of methane by anaerobic digestion; reactor conversion efficiencies; investigations on ethanol production from biodegradable municipal solid waste through hydrolysis and fermentation; hydrogen production from glucose through a hybrid anaerobic and photosynthetic process; biodiesel production from used cooking oil through base-catalyzed transesterification. Conversions by thermochemical processes are discussed in the subsequent eleven articles of the volume. These cover combustion, the direct use of heat energy; using the heat produced in thermal power stations for steam and, ultimately, electricity generation; municipal solid waste and refuse-derived fuel. In another article, computational fluid dynamics modelling is applied to assess the influence of process parameters and to perform optimization studies. A group of articles deal with more complex thermochemical processes involving combustion combined with pyrolysis and gasification. Two articles focus on biofuels as feed for fuel cells. In the last six articles, the emphasis is on management and policy rather than technical issues.